Swedish press council 1916-1987 - Weibull, Lennart; Börjeson, Britt (University of Gothenburg, 2025)
'Swedish Press Council 1916-1987' was part of the research project 'Publicistisk Sed'. The study is based on a review of the archives of the Press Council and the Press Ombudsman. Based on diaries and archived documents for each case, information has been transferred to a code scheme for data processing. The study focuses on the cases that have been received by the Swedish Press Council and the Press Ombudsman during the years 1916 to 1987. This means that all cases received have been coded, regardless of whether they have been formally processed or not. Even cases that have been written off directly have thus been considered part of the work performed.
In order to gain some knowledge of the role played by individual newspapers, the name of each newspaper reported has been recorded. This information, together with information on the year and decision in the case, has been collected in a separate file.

'Pressens Opinionsnämnd 1916-1987' var en del av forskningsprojektet 'Publicistisk Sed'. Studien grundas på en genomgång av Pressens Opinionsnämnds och Allmänhetens Pressombudsmans arkiv. Med utgångspunkt från diarier och arkiverade handlingar för varje ärende har uppgifter överförts till ett kodschema för databehandling. Studien är inriktad på de ärenden som inkommit till Pressens Opinionsnämnd och Allmänna Pressombudsman under åren 1916 till 1987. Detta innebär att alla inkomna ärenden kodats, oberoende av om de i formell mening behandlats eller ej. Även de ärenden som avskrivits direkt har således betraktats som en del av utfört arbete.
För att i någon mån få kunskap om vilken roll enskilda tidningar spelat, har namnet på varje anmäld tidning antecknats. Denna uppgift har tillsammans med uppgift om år och beslut i ärendet samlats i en särskild datamängd.
Pressens opinionsnämnd 1916-1987
Keywords: OMBUDSMEN; OMBUDSMÄN; PRESS; PRESS; Media; Media; Social Sciences; Samhällsvetenskap